Protected areas and extractive hegemony: A case study of marine protected areas in the Qikiqtani (Baffin Island) region of Nunavut, Canada. Issue 120 (March 2021) - Bernauer, Warren; Roth, Robin
Abstract: This article contributes to scholarly debates about the role of conservation in the reproduction of capitalist social relations with a case study on marine protected areas in the Canadian Arctic. Unlike historic parks in Canada, and modern parks in the Global South, new parks and protected areas in Canada are not cases of 'primitive accumulation' or 'accumulation by dispossession'. Drawing on Gramscian historical materialism, we argue that their relationship to capital accumulation is primarily one of legitimization. Protected areas play a complex and contradictory role in the reproduction of capitalism in northern Canada. Because they protect important wildlife habitat and hunting grounds from extraction, and insofar as they usually entail support for fishing and hunting practices, the establishment of new protected areas can help reproduce Indigenous hunting and fishing economies. They therefore help maintain the conditions of possibility for a future anti-capitalist and decolonial social transformation. Moreover, because protected areas remove land from extractive capital's sphere of activity, their establishment entails real material concessions to Indigenous communities from extractive capital. However, in the absence of a clearly articulated program for a broader social transformation, these concessions help create the conditions for Indigenous peoples to consent to an economy based on extraction and are therefore fundamental to the hegemony of extractive capital in Northern Canada. Thus, protected areas are part of an unstable equilibrium of compromises that extractive hegemony is premised on.